Self Presentation as Subjective Stancetaking in Celebrity Interview Show - Kyrychuk, Laryssa; Киричук, Лариса (Східноєвропейський національний університет імені Лесі Українки, 2014)
The paper explores the issues of self-presentation in celebrity interview show from the viewpoint of stancetaking theory. The research is focused on the analysis of self-presentational motivations, the ways of public image reinforcement / modification and communicative characteristics of the celebrity interview show. It specifies the factors that affect celebrity‟s subjective stancetaking as a verbal act of self-presentation in this type of social interaction. It is claimed that the tactics of self-presentation such as self-enhancement and self-criticism are realized through the selfacclaiming and self-disclaiming stancetaking correspondingly. These stance patterns are treated as indirect indexes of speaker‟s social personality and are linked to the acts of performance which are aimed at impression management. The celebrity‟s stancetaking is also regarded in the paper as a way of his/her self-construction. The method applied in the research is discourse analysis. У статті висвітлено питання саморепрезентації знаменитості в інтерв‟ю-шоу з погляду теорії позиціонування. Дослідження зосереджене на вивченні мотивації саморепрезентації, способах посилення модифікації іміджу та комунікативних характеристиках інтерв‟ю-шоу зі знаменитістю. У роботі визначаються фактори, які впливають на суб‟єктивне позиціонування як мовленнєвий акт саморепрезентації в цьому типі соціальної взаємодії. Стверджено, що такі тактики cаморепрезентації, як самопосилення і самокритика, реалізуються, відповідно, через самосхвалення і самозаперечення позиціонування. Такі моделі позиціонування трактуємо як непрямі показники соціальної особистості мовця і пов‟язуємо з демонстративними діями, мета яких – контроль за здійснення впливу. Позиціонування знаменитості також трактуємо як спосіб її самоконструювання.Головним методом дослідження є дискурсивний аналіз.
Саморепрезентація як суб’єктивне позиціонування в інтерв’ю-шоу зі знаменитістю.
Keywords: self-presentation; public image; stancetaking; verbal behavior; speech identity; саморепрезентація; імідж; позиціонування; мовна поведінка; мовна ідентичність